The impact of marketing strategies on green products purchasing behaviour : a study on Malaysian consumers' perspectives - Meysami, Vahid (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The aim of this study is to examine the impact of marketing strategies on green products purchasing behaviour from the perspective of Malaysian consumers. In this research we will examine the impact of green attitude, green advertising and green product pricing on Malaysian green purchase behaviour. This research proposes a conceptual model, based on the theory of planned behaviour (TPB) which has been introduced by Icek Ajzen (1985). This theory examines the relationship between attitude, subjective norms, perceived behavioural control and their impact on behaviour generally and on purchasing behaviour particularly. This study uses the theory of planned behaviour in the context of Malaysia to examine the Malaysian consumers' behaviours toward green products. Data was collected from 300 local Malaysians. The questionnaires were structured using a convenient sampling method to collect data mostly from famous shopping malls in the Klang Valley area. The empirical findings of this research supported all of the proposed hypotheses. The three dimensions shows the positive and significant impact of green attitude, green advertising and green product pricing on Malaysian green purchasing behaviour. Based on this research finding, green attitude and green advertising are the most influential factors impacting Malaysian green purchase behaviour. Theoretically this study support the theory of planned behaviour propounded by Icek Ajzen (1985), in which green advertising is considered as a subjective norm and green product pricing is adopted as a planned behavioural control. Researchers might implement this study for their future research and also marketers may conduct the result of this study to develop their marketing strategies in Malaysia. The findings also provide insight for knowledge seekers, by highlighting the Malaysian society's green tendency and their green lifestyle.